Analysis of Potentials and Strategies to Empower Sustainable Tourism in Burai Tourism Village, Ogan Ilir Regency - Shomedran, Shomedran; Saputra, Ardi; Sulistiono, Eko (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2023)
Burai Village has quite potential for tourism, supported by natural resources and human resources. This tourist object is known as the Burai Tourism Village which is a tourist object developed by displaying natural beauty such as flowing rivers, culture, religion, skills products and attractive colorful building forms. It is not impossible that there is potential that can still be developed for the sustainability of the Burai Tourism Village. Therefore, potential mapping is useful for inventory and analysis of tourism potential in Burai Village. The purpose of this study is to see the potential and mapping of development strategies that can be carried out for Burai Village. The method used in this study is a qualitative method with descriptive analysis to identify and explore the tourism potential, development, characteristics, and management of Burai Village. The results of the study show that Burai Tourism Village has enough potential resources, both natural, human resources, religion, skills and socio-cultural products as a tourist attraction. Burai Village in principle does not yet have a permanent sustainable tourism development strategy, it is necessary to structuring existing tourist attractions and uniqueness, as well as strengthening human resources, so that it is necessary to develop aspects of service, promotion, development of creative industries and tourism physical facilities.